Consumption Growth Persistence and the Stock–Bond Correlation - Jones, Christopher S.; Pyun, Sungjune (Journal of Financial and Quantitative Analysis, 2025)
Abstract We consider a model in which the correlation between shocks to consumption and to expected future consumption growth is nonzero and varies over time. We validate this assumption empirically using the model’s implication that time variation in consumption growth persistence (CGP) drives the correlation between stock and bond returns. Our model implies that the stock–bond correlation is also related to the predictive relation between bond yields and future stock returns. Finally, we provide suggestive evidence that asset price fluctuations are the primary driver of changes in CGP.